2006
DOI: 10.1038/sj.bmt.1705285
|View full text |Cite
|
Sign up to set email alerts
|

Increased intensity of acute graft-versus-host disease after reduced-intensity bone marrow transplantation compared to conventional transplantation from an HLA-matched sibling in children

Abstract: Eight children underwent reduced-intensity stem cell transplantation (RIST) from an HLA-matched sibling. They received a fludarabine-melphalan based preparative regimen. Stem cell source was bone marrow, and GVHD prophylaxis consisted of cyclosporine A alone. Acute GVHD grade II-IV and grade III-IV were observed in four (50%) and three (37.5%), respectively, out of these eight patients. This incidence was significantly higher than that after conventional bone marrow transplantation, without severe tissue damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…Although the lack of large and/or randomized studies about RIC and MAC [14], we reported that ovarian function was 81% (9/11) preserved after HSCT with RIC [8]. Although severe GVHD has been reported in RIC [15], no patients in our report have severe GVHD.…”
Section: Discussioncontrasting
confidence: 51%
“…Although the lack of large and/or randomized studies about RIC and MAC [14], we reported that ovarian function was 81% (9/11) preserved after HSCT with RIC [8]. Although severe GVHD has been reported in RIC [15], no patients in our report have severe GVHD.…”
Section: Discussioncontrasting
confidence: 51%
“…More recently, a Japanese team published its experience comparing conventional matched sibling allo-BMT following myeloablative conditioning regimen to reduced-intensity allo-BMT in children with different solid tumors performed between 1994 and 2005. 11 There were five neuroblastoma patients in the conventional/myeloablative conditioning group; however, the paper focuses on the incidences of acute GVHD and details concerning the outcome of neuroblastoma patients were not provided.…”
Section: Conventional Allo-hsctmentioning
confidence: 99%